The Effect of Inflammatory Cytokines in Alcoholic Liver Disease - Kawaratani, Hideto; Tsujimoto, Tatsuhiro; Douhara, Akitoshi; Takaya, Hiroaki; Moriya, Kei; Namisaki, Tadashi; Noguchi, Ryuichi; Yoshiji, Hitoshi; Fujimoto, Masao; Fukui, Hiroshi (Mediators of Inflammation, 2013)
Alcohol is the most common cause of liver disease in the world. Chronic alcohol consumption leads to hepatocellular injury and liver inflammation. Inflammatory cytokines, such as TNF-α and IFN-γ, induce liver injury in the rat model of alcoholic liver disease (ALD). Hepatoprotective cytokines, such as IL-6, and anti-inflammatory cytokines, such as IL-10, are also associated with ALD. IL-6 improves ALD via activation of the signal transducer and activator of transcription 3 (STAT3) and the subsequent induction of a variety of hepatoprotective genes in hepatocytes. IL-10 inhibits alcoholic liver inflammation via activation of STAT3 in Kupffer cells and the subsequent inhibition of liver inflammation. Alcohol consumption promotes liver inflammation by increasing translocation of gut-derived endotoxins to the portal circulation and activating Kupffer cells through the LPS/Toll-like receptor (TLR) 4 pathways. Oxidative stress and microflora products are also associated with ALD. Interactions between pro- and anti-inflammatory cytokines and other cytokines and chemokines are likely to play important roles in the development of ALD. The present study aims to conduct a systemic review of ALD from the aspect of inflammation.